Investigating stress measurement capabilities of GHz Scanning Acoustic Microscopy for 3D failure analysis. (September 2016) - Khaled, A.; Brand, S.; Kögel, M.; Appenroth, T.; De Wolf, I.
Abstract: This paper discusses the possibility of using Scanning Acoustic Microscopy in GHz frequencies for detection and analysis of stresses around TSVs. An innovative idea was employed to measure the slight variations in Rayleigh wave velocities as a function of Si crystal orientation using a spherical imaging lens. The fringe pattern around an empty TSV and a copper TSV was analyzed in different directions and Rayleigh wave velocities were calculated. The initial comparison between the measured velocities around the TSVs and the calculated values from a pure Si Crystal suggest the capability of using this technique in detecting Rayleigh wave velocity differences and thus, measuring stresses around Cu TSVs. Highlights: Discontinuities in the Si surface will generate fringes under acoustic inspection which might be used for failure analysis. Rayleigh wave interaction with Si crystal anisotropy generates non-circular fringes around TSVs. Rayleigh velocity increases after filling the TSV with copper.